Enhancing IPsec Performance in Mobile IPv6 Using Elliptic Curve Cryptography - Supriyanto Praptodiyono; M. Iman Santoso; Teguh Firmansyah; Ali Abdurrazaq; Iznan H. Hasbullah; Azlan Osman (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
Internet has become indispensable to the modern society nowadays. Due to the dynamic nature of human activities, the evolving mobile technology has played a significant role and it is reflected in the exponential growth of the number of mobile users globally. However, the characteristic of the Internet as an open network made it vulnerable to various malicious activities. To secure communication at network layer, IETF recommended IPsec as a security feature. Mobile IPv6 as the successor of the current mobile technology, Mobile IPv4, also mandated the use of IPsec. However, since IPsec is a set of security algorithm, it has several well-known weaknesses such as bootstrapping issue when generating a security association as well as complex key exchange mechanism. It is a well-known fact that IPsec has a high overhead especially when implemented on Mobile IPv6 and used on limited energy devices such as mobile devices. This paper aims to enhance the IPsec performance by substituting the existing key exchange algorithm with a lightweight elliptic curve algorithm. The experiments managed to reduce the delay of IPsec in Mobile IPv6 by 67% less than the standard implementation.